USE OF A GEOGRAPHIC INFORMATION SYSTEM FOR MAPPING WATER SUPPLY AND ECOSYSTEM SERVICES IN BANJAR REGENCYSOUTH KALIMANTAN PROVINCE - Rahman, Abdur; Rahman, Mijani; Hamdie, Badaruddin; Purnomo, Joko; Riduan, Rony; Kadir, Syarifuddin; Herliwati, Herliwati (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2025)
This study aims to analyze ecosystem services based on water availability ecosystem services in Banjar Regency, covering an area of 261,803.337 Ha including Suitable areas located in the Eastern and Western areas of Banjar Regency which include the villages; Rantau Bujur, Artain Belangian, Belimbing Lama, Rantai Balai, Bunglai, Benua Riam, Part of Aranio, East Mandiangin, Nyiur Island, West Mandiangin, in the West; located in the West in Aluh-Aluh District located in the villages; Sei Musang, Handil Purai, Gantung Papuyu, Tambak Sirang, Gambut Village, Tatah Layap, Balayung Village, Lok Buntar, Pematang Panjang, Bangkal River, Pembatanan, Bakung River, Lok Baintan Dalam, Batang Ilir River, Rangas Hambuku River. In the North area, most of the Unsuitable areas are 175,052.57 Ha located in the villages; Batik/batik/pandahan, Sawahan, East Jejangkit, Rasau River, Sukaramai, Pinang Island, Alalak Padang, Makmur Karya, Sumbersari, Pematang Danau, Kaliukan, Limamar, Bangkal River. The total area suitable and unsuitable for Water Availability Ecosystem Services is 436,855.907 Ha